Economic Growth and Income Inequality in Indonesia: A Systematic Review and Meta-Analysis of Two Decades of Research - Evi Syuriani Harahap; Imamul Khaira (Outline Publisher, 2025)
The relationship between economic growth and income inequality is a central policy challenge in Indonesia. This article presents a systematic review and qualitative meta-analysis of 21 empirical studies (2007-2025) examining this nexus at national and sub-national levels. The analysis reveals a lack of consensus on the direction of causality, with different studies supporting conflicting or insignificant relationships. Similarly, the validity of the Kuznets Curve hypothesis is found to be context-dependent, holding true in some provinces but not others. The review also identifies crucial mediating factors, including financial inclusion, education, and governance, which significantly influence the growth-inequality dynamic. Overall, the findings underscore the complexity of this relationship, calling for a policy shift away from a purely growth-centric paradigm towards more inclusive and regionally-tailored development strategies to ensure equitable outcomes.